STRUCTURAL ANALYSIS OF SEMI-SUBMARINE MONOHULL SHIP FOR TOURISM APPLICATIONS BY USING FINITE ELEMENT METHOD - Christian Imanuel Hutagalung; Aldias Bahatmaka; Widya Aryadi; Musdika Bagas Satria Putrananda; Berliana Ayarent Puteri (Rekayasa Mesin)
The research assesses the structural integrity of a semi-submersible monohull glass-bottom vessel designed for tourism, featuring a hull length of 9 meters. Finite Element Analysis (FEA) was employed to simulate five loading scenarios: full load, 75% capacity, 50% capacity, 25% capacity, and no load. The ship's structural basis was designated as the boundary condition. The peak equivalent stress under full load was 297.58 MPa, with validated values at 293.93 MPa. Additional scenarios demonstrated comparable concordance between FEA simulations and validations, with stress values spanning from 296.85 to 297.4 MPa and validation results ranging from 293.4 to 293.79 MPa. All calculated safety factors surpassed 2.25, guaranteeing adherence to SOLAS Chapter II-1 rules. The results validate that the ship's hull design complies with structural integrity norms under operational loads, instilling confidence in its performance for tourism purposes.